2013
DOI: 10.5267/j.ijiec.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi criteria decision making methods for location selection of distribution centers

Abstract: In recent years, major challenges such as, increase in inflexible consumer demands and to improve the competitive advantage, it has become necessary for various industrial organizations all over the world to focus on strategies that will help them achieve cost reduction, continual quality improvement, increased customer satisfaction and on time delivery performance. As a result, selection of the most suitable and optimal facility location for a new organization or expansion of an existing location is one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Ballı and Korukoglu [68] and Chakraborty et al [69] suggested using both the Spearman and Kendall tau correlation tests to examine the correlation of two rankings (the results of Tables 3 and A5). The calculated results show that the Spearman correlations and the Kendall coefficient were 0.981 and 0.9, respectively.…”
Section: The Results Of Sensitivity Analysismentioning
confidence: 99%
“…Ballı and Korukoglu [68] and Chakraborty et al [69] suggested using both the Spearman and Kendall tau correlation tests to examine the correlation of two rankings (the results of Tables 3 and A5). The calculated results show that the Spearman correlations and the Kendall coefficient were 0.981 and 0.9, respectively.…”
Section: The Results Of Sensitivity Analysismentioning
confidence: 99%
“…In the literature, studies on problem of DCs' location selection under certainty have focused on three categories of solution techniques [35] (see Table 1 the problem in question. We cite the method based on Analytic Hierarchy Process (AHP) and -means method [11] and the method based on REGIME [12]. The methods in this first category are used in the case where the number of predetermined alternatives are limited.…”
Section: Related Methodsmentioning
confidence: 99%
“…Multicriteria decision-making Method based on AHP and -means method Simić et al [11] Method based on REGIME Chakraborty et al [12] Metaheuristics for the multiobjective decision-making…”
Section: Proposed Bymentioning
confidence: 99%
See 1 more Smart Citation
“…It was also used in the process selection in the manufacturing sector (Parkan & Wu, 1998) and performance measurement in government services (Parkan, 1999). Other issues where OCRA has been used are as follows: robot selection (Parkan & Wu, 1999), measurement of the performance of an investment bank (Parkan & Wu, 1999), competitive analysis of manufacturing plants of processed food industry (Jayanthi et al, 1999), measurement of the operational performance of a public transit company (Parkan, 2002), the performance of drugstore operations (Parkan, 2003), gauging the performance of a supply chain (Parkan & Wang, 2007), location selection of distribution centers (Chakraborty et al, 2013), material selection (Chatterjee & Chakraborty, 2012;Darji & Rao, 2014), and performance analysis of public banks in Turkey (Ö zbek, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%